Automatic transmissions and transaxles - Erjavec, Jack (Today's technician, 2007)
Offering a technician-oriented coverage, this work helps users to understand the design, construction, troubleshooting techniques, and service procedures. It features an introduction to continuously variable transmissions (CVT), and also offers coverage of drivelines for front-wheel drive (FWD) and four-wheel drive (4WD) vehicles.